Public Penetrations: Jesús Rafael Soto’s Entry into Political Art - Corso, John (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2013)
Venezuelan artist Jesús Rafael Soto led Latin America’s innovative kinetic art movement of the 1960s with his Plexiglas moiré reliefs and geometric installations. The current literature predominantly describes his work in terms of formalism or phenomenology. However, his work also brings together social agents in public spaces, and this raises the issue of the political. Using the critical theory of Hannah Arendt, this paper recasts Soto’s so-called Penetrable sculptures from the 1960s and 1970s as political interventions through which he reintroduces a viable public sphere of action in the midst of Venezuela’s thorny recovery from totalitarianism.